Niveles de alcoholemia en conductores involucrados en accidentes de tránsito, Región de Salud PNP La Libertad, Agosto 2016 - Enero 2017 - Burgos Velarde, Jesús María (2018)
The present study was aimed at determining blood alcohol levels using the Conway Micro diffusion Technique in blood samples of people of both sexes involved in traffic accidents investigated by all PNP units (National Police of Peru) of the La Libertad Region. Performed in the Ethical Dose Service of the PNP Health Region of La Libertad, from August 2016 to January 2017. There were 5680 involved in traffic accidents, having 1454 (25%) positive and 4226 (75%) negative; Of the positive blood alcohol content, 98.5% were males and 1.5% females; When the result of Breathalyzer (positive BAC and BAC) was correlated with sex, with Pearson's Chi square test and with a level of significance of 0.05, it was shown that they are not correlated